On the convergence of positive increasing functions to infinity - Buldygin, V. V.; Klesov, O. I.; Steinebach, J. G. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study the conditions of convergence to infinity for some classes of functions extending the well-known class of regularly varying (RV) functions, such as, e.g., O-regularly varying (ORV) functions or positive increasing (PI) functions.